The Effectiveness and Students’ Respond Toward Exercise-Based Textbook of Morphology in Online Learning - Sutarman Sutarman; Wirajaya Kusuma; Zainudin Abdussamad; Titik Ceriyani MIswaty; Wahyu Kamil Syarifaturrahman (Humanitatis : Journal of Language and Literature, 2024)
Online learning is currently one of the lecture models that is widely applied on various campuses. However, learning control raises a problem so a solution is needed to maintain the quality of learning. This study aims to test the effectiveness of textbooks in online learning in morphology courses. The method used is a mix of quantitative and qualitative methods. to assess the feasibility of textbooks, researchers distributed questionnaires to students. statistical test results showed that there is a significant influence between the use of exercise-based textbook with students’ learning outcomes (Sig. = 0.021<0.05) in which class B who used textbooks scored 81.190 or higher than class A who did not use textbooks with a score of 70.727. Students’ response to the textbooks used are 71% good so that the textbook is suitable for use as textbooks. Thus, the use of exercise-based textbook on online learning in morphology courses is very helpful in improving the quality of learning.